MODIFIKASI STEREOTIP GENDER PEREMPUAN PADA TAYANGAN KULINER DI TELEVISI (STUDI HEGEMONI IDEOLOGI GENDER DALAM PROGRAM “ALA CHEF” TRANS TV VERSI FARAH QUINN) - SARI MONIK AGUSTIN (Communication, 2013)
This writing aimed to describe how the woman’s gender-stereotype transformation in the culinary television program. The particular TV Program was “Ala Chef” Trans TV hosted by Farah Quinn, a chef who’s also a model. The focus of this writing is the comparison between Farah Quinn and Sisca Soewitomo, a host of culinary program in earlier era.The frameworks used in this writing were Gramsci’s thought of Hegemony and Connell’s Gender Hierarchy of Hegemonic Masculinity. Besides, the explications of concepts such stereotype, gender, ideology, gender-stereotype, gender ideology occured as additional analysis tools.The conclusion showed gender ideology hegemony occured through partriachy values spreading in institutions, particularly mass media such as television program. Culinary program was one of the program that perpetuated gender ideology. Program such as “Aroma” and “Ala Chef” had different format, but this paper showed that the different format was only transformation done by traditional intellectual in perpetuating the ideology. Mass media and popular culture content, eventually, abide to hegemonic production, reproduction and transformation. There was no counter-hegemony founded in this paper. Farah Quinn as a part of intellectuals was failed to counter the hegemony and to be a resistant femininity. Although, Farah Quinn was a career woman and an intellectual chef, she was still a traditional intellectual when she perpetuated the gender ideology in different form.